Poling and depoling influence on the micro-stress states and phase coexistence in KNN-based piezoelectric ceramics. Issue 4 (April 2019) - Val-Gómez, P.; del Campo, A.; Rubio-Marcos, F.; Fernández, J.F.; Moure, A.
Abstract: In this work a microstructural qualitative and quantitative study of spatial stress distributions in modified KNN ceramics (K0.44 Na0.52 Li0.04 )1-x Cox/2 (Nb0.86 Ta0.10 Sb0.04 )O3, according to the polarization state is shown. X-ray diffraction reflects a perovskite crystalline structure with coexistence of Tetragonal and Orthorhombic phases (T/O). Confocal Raman microscopy shows that these crystalline phases are distributed in randomly micrometric regions through the ceramic volume. Tetragonal regions show higher piezoelectric coefficient and exhibit a higher micro-stress that hardens the ferroelectric response. By the contrary, the occurrence of orthorhombic micro-regions softened the ferroelectric behavior and reduced their piezoelectric coefficients. The ferroelectric response of ceramics is studied, where poling is also shown as a factor that affects the spatial micro-stress distributions. Finally, a model that relates the results obtained by Raman characterization with the ferroelectric properties and stress states is proposed.